CONSULTATIVE FUNCTION MONITORING AGENCY VILLAGE (BPD) PNPM Mandiri THE IMPLEMENTATION OF RURAL VILLAGE IN THE DISTRICT MANDOLANG KALASEY DISTRICT MINAHASA - Takasily, Natalia Gledis; LALOMA, ALDEN; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :Village Consultative Body (BPD) is one of the perpetrators of PNPM Rural in the village which serves as the agency that oversees the process of each stage desa.Tujuan PNPM Rural in this study to determine how the function of BPD supervision of the implementation of PNPM Rural Village Kalasey One Subdistrict Mandolang Minahasa.The method used is descriptive qualitative method. The focus of research is supervision of BPD at the planning and implementation stages of PNPM Mandiri in the village. Informants were taken from perpetrators PNPM Rural Village Kalasey One, entirely as many as 10 people. Data collection techniques used were interviews. Data analysis technique used is descriptive-qualitative analysis interactive model of Miles and Hubernann.Based on research results ditariki conclusions: (1). BPD supervisory functions in the planning activities of PNPM Rural done fairly well, namely through the activity of BPD in every stage of the planning of activities ranging from the preparation and dissemination of early, stage of planning at the village and district. (2) The oversight function of BPD at the stage of implementation of PNPM Mandiri in the village is quite well done is through the activity of BPD in each stage of the start of the preparatory meetings implementation in the village, distribution and use of funds, procurement of labor, materials and tools, monitoring and evaluate progress on implementation of activities in the field, and village meetings for accountability by the implementation team.Based on the results of this penellian then it can be recommended some suggestion that: although PNPM Mandiri is no longer there, but the results achieved must be maintained and preserved to support the efforts penanggunglangan poverty. For that BPD oversight function to be needed in the maintenance and preservation of the results of PNPM Mandiri.Keywords: Monitoring, BPD, PNPM Mandiri.